Leadership BS fixing workplaces and careers one truth at a time - Pfeffer, Jeffrey (New York HarperCollins Publishers, 2015)
The leadership industry has failed,' charges Stanford Business School professor Pfeffer in this lively critique of a professional discipline driven, according to him, not by wisdom or a desire to foster leadership, but by money. Its precepts, he writes, are 'based more on hope than reality, on wishes rather than data, on beliefs instead of science.' Pfeffer sets out to help his readers rethink leadership by focusing on the root causes of failures in business leadership. Pfeffer counsels readers to look away from the 'inspiration and fables' that glut the market, and to accept that some of those truisms are fallible: authenticity can be overrated, and honesty is not always the best policy for leaders. Pfeffer has taken on an ambitious project, given the uniformity of current thinking on business success, but his bluntness should go a long way toward slaughtering the sacred cows of the leadership industry
Includes index
Keywords: Leadership